Aproveitamento do resíduo do processamento de mamão formosa (Carica papaya L.) e otimização do método de secagem por spray drying - Maciel, Elizeny de Fátima Soares (2024)
During the processing of papaya, large quantities of by-products are generated, such as peels and seeds, which have potential for use. The aim of this study was to dry and optimize the drying process of formosa papaya waste (peels and seeds) using the spray drying method, using orthogonal central composite experimental design. The independent variables studied were the temperature of the drying air (105-130ºC), the flow rate of the solution fed into the dryer (0.4-0.8 L/h), the flow rate of the drying air (1.6-1.8 m3/min) and the concentration of maltodextrin (5-20%) in an attempt to identify the best operating conditions that would provide satisfactory physicochemical and nutritional properties for the dried papaya residue. The results showed that the papaya waste powders obtained had low humidity, with values of less than 3.5%. In addition, the water activity ranged from 0.114 to 0.293. It was found that the presence of maltodextrin contributed significantly to reducing the hygroscopicity of the powders. In terms of yield, it was found that higher concentrations of maltodextrin combined with higher temperatures produced higher yields. With regard to color, there was a tendency for greater luminosity with lower temperatures and higher levels of additive agent. It was found that the dried material was lighter than the fresh material, probably due to the addition of maltodextrin. The values found for total acidity, in general, were relatively low, which translates into sweetness for the material. The highest value of ascorbic acid content obtained in the study was 0.32 mg-100 g-1 (b.s.). When high drying air flow rates and low temperatures were adopted, the concentration of phenolics increased. The flavonoid content tended to increase with higher concentrations of maltodextrin. With regard to total carotenoid values, the highest value obtained was 71.21 μg/g in the condition with the lowest maltodextrin concentration. Obtaining papaya waste powder in a spray dryer indicates that it is possible to use it while preserving its bioactive properties.